2016
DOI: 10.3329/jbau.v13i2.28786
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood improvement through family poultry farming in Mymensingh district

Abstract: The present study was done to examine the employment and income generation of small farmers through family poultry. The objectives of the study were to identify socio economic features of family poultry, to examine the impact of family poultry on household improvement, to determine cost, return and profitability of family poultry, to identify the problems faced by family poultry farmer and for its improvement. The data were collected from 90 family poultry farms from Sadarupazila and Trishalupazila of Mymensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 1 publication
5
19
0
Order By: Relevance
“…Findings from Rufiji district (Tanzania) showed that poultry production increased income of families and provide protein to local communities adjacent to the Selous Game Reserve [5]. This is in agreement with other studies such as [7,12], which showed that, through accessibility of food, employment and income from poultry production, family livelihood is improved. During our study, we noticed one chicken costs Tanzanian shillings 15,000/= (equivalent to 7USD) which implies that, if local communities are supported via chicken production in these villages, they are able to generate a basic income that caters for school fees for kids, clothing, food, shelter and health care.…”
Section: The Biodiversity In the Magombera Forestsupporting
confidence: 77%
See 2 more Smart Citations
“…Findings from Rufiji district (Tanzania) showed that poultry production increased income of families and provide protein to local communities adjacent to the Selous Game Reserve [5]. This is in agreement with other studies such as [7,12], which showed that, through accessibility of food, employment and income from poultry production, family livelihood is improved. During our study, we noticed one chicken costs Tanzanian shillings 15,000/= (equivalent to 7USD) which implies that, if local communities are supported via chicken production in these villages, they are able to generate a basic income that caters for school fees for kids, clothing, food, shelter and health care.…”
Section: The Biodiversity In the Magombera Forestsupporting
confidence: 77%
“…These alternative sources include poultry and other livestock production, crop cultivation, beekeeping, and tourism ventures. Kabir et al [7] showed that poultry production has several advantages over other livestock keeping. Among these benefits are improved livelihood, high growth rate, market availability, adaptation to different climatic conditions, and production of quality protein with less cholesterol than other livestock keeping [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are ten hatcheries in the province compared to 273 poultry enterprises/projects (CSO, 2017). The respondents put this constraint as fourth in rank, in line with findings of Adetayo et al,(2013); Mendes et al, (2014);Ali et al, (2015); Kabir et al, (2015) and Onono et al, (2018).…”
Section: Discussionsupporting
confidence: 85%
“…Modern intensive and semi-intensive poultry production requires high capital investment. Among financial constraints, Poultry producers ranked lack of capital as fourth, which is in line with results of Kabir et al, (2015) and Hassan et al, (2016).…”
Section: Discussionsupporting
confidence: 73%